Urine β2-Microglobulin and Retinol-Binding Protein and Renal Disease Progression in IgA Nephropathy - Shen, Xiaoqi; Cheng, Jun; Yu, Guizhen; Li, Xiayu; Li, Heng; Chen, Jianghua (Frontiers in Medicine, 2021)
Background: Tubulointerstitial involvement has been reported to have a decisive influence on the progression of IgA nephropathy (IgAN). High levels of urine β2-microglobulin (β2-MG) and retinol binding protein (RBP) were observed in IgAN patients with tubulointerstitial lesions. However, their roles in disease progression remain unclear. This study aimed to evaluate the associations of urine β2-MG and RBP with progression of IgAN. Methods: We retrospectively investigated a cohort of 2153 patients with IgAN. Clinical and pathological features, outcomes and urine β2-MG and RBP at the time of biopsy were collected. The associations of urine β2-MG and RBP with composite renal outcome, defined as a decline in estimated glomerular filtration rate (eGFR) of ≥ 50% from baseline or end stage renal disease (ESRD) were examined using restricted cubic splines and Cox models. Results: During a median follow-up of 20.40 months, 140 (6.50%) patients reached composite renal outcomes. Restricted cubic splines showed that patients with higher urinary β2-MG and RBP levels had worse renal outcomes. Cox regression analysis revealed that urine β2-MG and RBP were associated with a risk of composite renal outcome in the multivariate adjusted model (+1 SD for log β2-MG, HR=1.462, 95% CI 1.136-1.882, P=0.003; +1 SD for log RBP, HR=1.972, 95% CI 1.486-2.617, P=0.001). The associations were detectable within patients with baseline eGFR＜90 ml/min/1.73m2 (+1 SD for log β2-MG, HR=1.657, 95% CI 1.260-2.180, P＜0.001; +1 SD for log RBP, HR=1.618, 95% CI 1.199-2.183, P=0.002), but not among patients with eGFR≥90ml/min/1.73m2. Conclusion: Higher levels of urine β2-MG and RBP were independent risk factors for renal disease progression in IgAN.